2019
DOI: 10.35787/jimdc.v8i2.361
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nigella Sativa on Oxidative Stress in Post-Menopausal Females

Abstract: Background: The permanent cessation of menstrual periods in menopause causes a decline in estrogen levels and increased oxidative stress. Both of these factors lead to menopausal symptoms, cardiovascular diseases and osteoporosis in the postmenopausal females that negatively affect the quality of their lives. Antioxidant properties of Nigella sativa are due to its natural ingredient “thymoquinone” and have been studied in various animal and human studies. This study was done to determine beneficial effect of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…group was significantly higher than that in the placebo group. This result is consistent with the result of a clinical trial conducted by Sana, Saeed, and Umair (2019), which indicated useful antioxidant effects of Nigella sativa L . on menopausal women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…group was significantly higher than that in the placebo group. This result is consistent with the result of a clinical trial conducted by Sana, Saeed, and Umair (2019), which indicated useful antioxidant effects of Nigella sativa L . on menopausal women.…”
Section: Discussionsupporting
confidence: 92%
“…In the present work, the mean score of post-intervention I-QoL in the Nigella sativa L. group was significantly higher than that in the placebo group. This result is consistent with the result of a clinical trial conducted by Sana, Saeed, and Umair (2019), which indicated useful antioxidant effects of Nigella sativa L. on menopausal women. These useful antioxidant effects could seemingly improve their QoL (Healthcare, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the consumption of Nigella sativa powder at 1 g/day in 30 postmenopausal women for 2 months caused a significant decrease in body weight (p = 0.012) and BMI (p = 0.011) as compared to the baseline. The supplement also increased glutathione (GSH) levels (p < 0.001) versus initial values, indicating reduction in oxidative stress and contributing to a better quality of life in these women [95].…”
Section: Effects Of Nigella Sativa In Menopausementioning
confidence: 99%